Gallbladder agenesis diagnosed during surgery - Vera-Portilla, Angel F. (2025)
Gallbladder agenesis (GBA) is an extremely rare disease that mimics biliary pathology. More frequent in women, it can occur alone or associated with other malformations. We present the case of a 53-year-old female patient with clinical symptoms compatible with cholelithiasis, with ultrasound reports of scleroatrophic gallbladder. Elective laparoscopic cholecystectomy was performed, with no gallbladder found, and intraoperative cholangiography was performed with the same results. Postoperative magnetic resonance cholangiography confirmed gallbladder agenesis. Finally, the postoperative course was adequate, without complications. GBA commonly presents with typical symptoms of biliary colic and ultrasound diagnosis of cholelithiasis or scleroatrophic gallbladder. Preoperative diagnosis is unlikely. If surgery is performed, laparoscopic examination is preferable. Subsequently, the evolution is generally asymptomatic.